Work as a common good in Indigenous communities in southern Mexico - Garza-Vázquez, Oscar (Journal of global ethics, 2025)
In recent decades, there has been a surge in proposals to measure ‘good quality’, ‘decent work’ for all as an intrinsic aspect of development. This article aims to contribute to this discussion, but from the perspective of a common good approach to development in the context of Indigenous communities in southern Mexico. Drawing on specialised literature about the social and collective organisation of work in these contexts, the article offers an ethical reflection on conceptions of work. It concludes that current indicators are biased towards (1) market-mediated, (2) outcome-oriented, (3) individual-based conceptualisations of work, and therefore provide a limited understanding of the nature of work and the social mechanisms that organise it in these communities. Therefore, building on the common good approach to development, the article proposes that work in these settings is best understood as a common good; a good that is valued, produced, sustained and enriched through the participation of all, for the benefit of all.